Development of automated system for rapid evaluation of coal deposits with application of universal system of representation of rocks, transition rocks and coal - Schejbal Ctirad (Acta Montanistica Slovaca, 2002)
The Geoinformatic section of Institute of geological engineering HGF VB-TU Ostrava is engaged a long time in the creation of coal databases, elaboration of automated systems of graphical presentation of exploration and/or mining data and in the development of automated system for rapid evaluation of coal deposits. This paper describes the main stages of problems solving, namely:− analysis of both classification and documentation systems of coal deposits,− creation of both structure and content of specialized databases,− principles of the selection of appropriate statistical/geostatistical procedures of geodata analysis,− proposal of the automated generation of both deposits documents and graphical symbols,− elaboration of the automated system for rapid evaluation of coal deposits.